Role of demographic Variables in Patients motivations towards Home Remedies: A Cross Sectional Study - Lall , Shatakshi (International Journal of Psychosocial Rehabilitation, 2018)
The use of home remedies is a widespread practice among patients seeking to alleviate various health issues. Nevertheless, the underlying reasons driving this practice remain poorly comprehended, particularly in regards to the impact of demographic factors. The purpose of this study, conducted in an urban area, was to explore the interplay between demographic factors and the underlying reasons that prompt patients to resort to natural remedies. Data was gathered through surveys administered to patients in various healthcare facilities, focusing on their demographic characteristics and rationale for employing natural remedies. The research accentuates the importance of examining demographic factors when analyzing patients' utilization of natural remedies. Healthcare practitioners can leverage these findings to provide more tailored care and guidance to their patients, while considering their individual demographic attributes and incentives for employing natural remedies.